A COMPARATIVE STUDY OF ENGLISH AND AWORI SUPRASEGMENTAL SYSTEMS - OLOWOFOYEKU, Peluolami; IWAENI , Ronke Dorcas; ADEBANJO , Mopelola Omowumi; YUSUF , Omolayo (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This study investigates the suprasegmental systems of English and Awori, a Nigerian language, with a focus on their phonological and phonetic properties. The research aims to identify similarities and differences between the two languages in terms of stress, intonation, tone, and rhythm. A comparative analysis of the suprasegmental features of both languages reveals distinct patterns and structures, shedding light on the unique characteristics of each language. The population of this study comprised he speakers of Awori in Ojo Local Government Area of Lagos State. Fifteen informants were selected from different age grades and sexes from whom a word list of 400 Basic Items in the Awori dialect was recorded and transcribed using the International Phonetic Association symbols. The result revealed that there were certain problems associated with the learning of Phonology by Awori speakers of English as a Second language specifically and Nigerian learners in general.